A randomised controlled trial comparing a thermal massager with artificial teardrops for the treatment of dry eye. Issue 1 (16th October 2013) - Lee, Ji-Eun; Kim, Na Mi; Yang, Jae Wook; Kim, Su Jin; Lee, Jong Soo; Lee, Ji Eun
Abstract : Background: To evaluate the efficacy and safety of a thermal massager for the treatment of dry eye syndrome. Methods: Ninety-five patients with dry eye syndrome were randomly assigned to receive either the thermal massager or artificial tears treatment. Thermal massage consisted of vibration, massage and thermotherapy and was carried out twice daily. Patients in the artificial tears group received 0.1% sodium hyaluronate solution five times daily. The Ocular Surface Disease Index (OSDI) score, break-up time (BUT), Schirmer test, fluorescein staining of the cornea, tear osmolarity test and adverse events were evaluated after 4 weeks. Results: OSDI showed a significant improvement in both groups and improvement was significantly greater in thermal massager group (p=0.032). BUT and fluorescein staining also indicated significant improvement. No differences were found between the two groups in measures other than the OSDI. Adverse events were mild and transient. Conclusions: Thermal massage was effective in improving dry eye syndrome both subjectively and objectively. It was safe and seems to be a useful treatment option.